ChemInform Abstract: Helical Oxidovanadium(IV) Salen‐Type Complexes: Synthesis, Characterization and Catalytic Behavior. Issue 12 (25th March 2014) - Barman, Sanmitra; Patil, Smita; Desper, John; Aikens, Christine M.; Levy, Christopher J.
Abstract Four oxidovanadium complexes, e.g. DCAP and BNBA, are prepared and tested as chiral catalysts for the oxidation of thioanisole (I) to sulfoxide (II).